KARAKTERISTIK PILIHAN MAKANAN DAN INFORMASI KANDUNGAN ZAT GIZI MAKANAN; STUDI MELALUI MEDIA SOSIAL INSTAGRAM - Valendra Haamiim; R Dwi Budiningsari; Abdul Wahab (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Characterizing food choices and nutritional information: study through social media instagramPurpose: Instagram is one of the popular social media platform that provide users to capture and share photos and videos. Instagram serves as an attractive choices to individuals intending to share photos of food they are consuming. Due to the popularity of Instagram, the availability of rich data can be analyzed and produce information. Using Instagram as a food photos database, researcher wants to identify characteristics dietary choices and nutritional information of food based on Instagram.Method: this study presents both qualitative and quantitative data. Qualitative data collection was conducted by semi structured interviews with 11 participants and qualitative data collection was taken from food photos database on Instagram with 400 samples.Results: Food items more extensively mentioned (n=291) 72,75% in Instagram post is high calorie food (554 calories). Instagram manifest consumption is characterized by high carbohydrate (154 grams) 54,25% (n=217), high fat (31 grams) 45,5% (n=182), high sodium (810 mg) 82% (n=328), low protein (16 grams) 65,75% (n=263), and low fiber (7 grams) 70% (n=280) food. There were no differences in food characteristics posts between male and female users (p=7,61).Conclusion: Characteristics of food posts on Instagram are classified as high calorie foods. The nutritional information of food posts on Instagram contains high carbohydrate, high fat, high sodium, low protein, and low fiber. Our participants choose to use Instagram because it provided an easier and more fun for food tracking and journaling. Participants can receive emotional support by finding others similar interested and social interaction between users and also gave them a way to self express through food photos.